Central Serous Chorioretinopathy from the Point of View of OCT-Angiography. Part 1. Chorioretinal Blood Flow Changes - A. G. Shchuko; S. I. Zhukova; T. N. Iureva; A. N. Zlobina (Oftalʹmologiâ, 2018)
Numerous recent studies indicate that the key mechanism for the development of central serous chorioretinopathy (CSR) is damage to retinal pigment epithelium (RPE). At the same time, the reports appeared in recent years indicate that an equally important link in pathogenesis is the disturbances of the choroidal blood flow. Thus, the introduction into clinical practice of optical coherence tomography in the angiography (OCTA) mode made it possible to visualize the retinal and choroidal vessels taking into account their segmentation, which opens up prospects for studying chorioretinal blood flow in the CSR. Purpose: to reveal the regularities of the change in the choroidal blood flow in patients with SCR according to the OCTA data, to assess their informativeness and role in the pathogenesis of the disease. Patients and methods: 26 patients with SCR aged 35–54 years were examined. To assess the chorioretinal blood flow, optical coherence tomography of the retina is included in the angiography mode in the scope of the diagnostic examination. Results and discussion: It has been revealed that the number of large vessels in the immediate vicinity of the RPE is increasing in SCR, i.e. the vessels move towards the retina in the direction of the least resistance. Disturbance of the hierarchy of the vasculature is an important fact, allowing to speak about pronounced hemodynamic disorders. Disturbance of the topography of large-caliber vessels is accompanied by the formation of a characteristic vascular pattern. The revealed predominance of the reticular pattern of large vessels in patients with CSR is more likely due to the presence of a significant number of bifurcations and anastomoses, as well as an increase in the proportion of crossed vessels. This may be accompanied by an increase in total vascular resistance. Consequently, the hydraulic resistance can increase at these sites, a turbulent blood flow occurs and the permeability of the vascular wall increases. Correspondence between changes in RPE and choriocapillaries was established. Taking into account that the RPE detachments from 450 to 780 (on average 515 ± 72.3) μm, revealed in the projection of the altered choriocapillaries, have comparable sizes with the value of one vascular lobe (515 × 450) μm, one can speak of a local lesion of choriocapillaries and RPE within one arteriocentric lobules. Conclusions: The revealed changes in regional blood flow are progressive and can be used as classification and prognostic criteria for choroidal dysfunction.